Unsteady axisymmetric radiative Cu-Al2O3/H2O flow over a radially stretching/shrinking surface - Khashi’ie, Najiyah Safwa; Md Arifin, Norihan; Pop, Ioan (Elsevier B.V., 2022)
The unsteady stagnation point flow of hybrid nanofluid past an impermeable disk is investigated with the presence of thermal radiation. The pair of aluminium oxide and copper with 2% of φhnf are numerically analyzed using the existing correlations of hybrid nanofluid. The governing model is simplified into a set of differential (similarity) equations and then, numerically solved by employing the bvp4c solver in the Matlab software. The dual solutions are presented while the stability analysis certifies the physical/real solution. The availability of dual solutions is detected when the range of control parameters are 1.5 ≤ B ≤ 1 (unsteadiness decelerating parameter), 0 ≤ R ≤ 0.1 (radiation parameter) and λc ≤ λ ≤ 0.5 (velocity ratio parameter). The accession of radiation parameter and the use of different nanofluids (Cu-H2O, Al2O3-H2O and Cu-Al2O3/H2O) are not prolonging the boundary layer separation. However, the addition of R, B and the use of Cu-Al2O3/H2O hybrid nanofluid enhance the thermal performance of the working fluid.